IMPACT OF BANK REPUTATION, SERVICE QUALITY, AND SOCIAL MEDIA MARKETING ON CUSTOMER TRUST AND LOYALTY - Nida Adelia; Unggul Kustiawan (Journal of Applied Economics in Developing Countries, 2025)
Customer loyalty is a strategic factor that determines the long-term success of banks in an increasingly competitive market. This study investigates the influence of bank reputation, self-service technology quality, offline service quality, and social media marketing on customer trust and loyalty. The research applied a quantitative approach with PLS-SEM, using responses from 201 BCA bank customers. The results show that bank reputation and social media marketing contribute to building offline trust, while self-service technology and offline service quality strengthen both offline and online trust. In turn, customer trust significantly enhances loyalty. These findings suggest that banks should focus on enhancing both offline service quality and online engagement strategies to improve trust and loyalty, ultimately boosting their competitive edge in the evolving banking landscape.